ANALISIS PENGARUH RASIO BOPO, LOAN TO DEPOSIT, CASH RATIO TERHADAP PROFITABILITAS (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar Di BEI Dalam Kurun Waktu 2018 -2020) - Nangur, Dionisius Satria Wijaya; Pamungkas, Leo Dadyo (Journal Competency of Business, 2022)
Factors that affect profitability based on normal conditions when viewed in terms of liquidity, solvency, and activity, if the current ratio is high it will indicate a strong liquidity position and vice versa. This study aims to analyze the effect of the bopo ratio, loan to deposit, cash ratio on profitability. The population in this study are banks listed on the Bursa Efek Indonesia (BEI) for the 2018-2020 period. The sample banks in this study were 30 banks and the sample was determined using the purposive sampling method. The study used descriptive statistical analysis, classical assumption testing, Multiple Regression Analysis and analysis tools using SPSS 25 The results of this study indicate that, (1) BOPO has a negative effect on company profitability, this is indicated by the regression coefficient value of -0.073 with a significance value of 0.002 because the coefficient value is negative and the significance value is less than 0.05. (2) LDR has a positive positive effect on company profitability, this is shown by the regression coefficient value of 0.145 with a significance value of 0.000 because the coefficient is positive and the significance value is less than 0.05. (3) the cash ratio has no effect on the company's profitability, this is shown by a regression of 1.531 with a significance value of 0.485 because the coefficient is positive and the significance value is greater than 0.05.